Acute-phase response, clinical measures and disease activity in ankylosing spondylitis - Ozgocmen, Salih; Godekmerdan, Ahmet; Ozkurt-Zengin, Fatma (Elsevier France-Editions Scientifiques Medicales Elsevier, 2007)
Objective: The evaluation of disease activity in ankylosing spondylitis (AS) is sometimes difficult. In this study we assessed acute-phase reactants (APR) and immune response status (humoral and cellular) in active and inactive untreated AS patients categorized according to different activation/remission criteria. Methods: Patients with AS were categorized into three groups as active and inactive according to ASsessment in Ankylosing Spondylitis (ASAS) International Working Group remission/partial remission criteria, Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) less than 4 or equal or more than 4 and peripheral joint involvement present or absent. Health Assessment Questionnaire-Spondyloarthropathies (HAQ-S), Daugados Articular Index and Bath Ankylosing Spondylitis Functional Index were performed. Erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), immunoglobulin A, G and M, and complements C3 and C4, interferon-gamma, interleukin-4 and alpha-1-antitrypsin (AAT), alpha-2-macroulobulin, ceruloplasmin, haptoglobin, and transferrin were measured. Immunophenotypic analysis by flow cytometry was performed (CD45, CD3, CD4, CD8, CD4(+)/CD8(+) T cell ratio, CD19, CD16, CD56, CD23, CD25 and CD30 were assayed). Results: Patients with peripheral involvement had higher ESR and CRP levels. According to ASAS criteria patients in remission had significantly lower values of disease activity and functional limitation measures, and AAT was the only APR significantly lower in remission/partial remission group. Lymphocyte subpopulations did not show significant correlation with clinical parameters or APR. Conclusions: Our results showed weak a relation between APR and disease activity in AS; however, APR should not be disregarded in the evaluation of disease and/or response to the treatment, which was supported by the new research on biologic agents infliximab and etanercept in AS. The ASAS remission/partial remission criteria may discriminate patients' clinical activity status and AAT may be a good indicator of disease activity in AS. (C) 2007 Elsevier Masson SAS. All rights reserved.
Keywords: ankylosing spondylitis; lymphocyte subtypes; immunophenotyping; acute-phase reactant; alpha-1-antitrypsin; cytokine; T helper